Election Prediction On Social Media - Singh, Praveen Kumar; Seetha, Anurag (International Journal of Computer Sciences and Engineering, 2025)
Social media today is the most popular medium of communication, due to its immediacy. According to Statista, the number of social media users in India is 226 million (2018) and this is expected to go up to 336 million by 2021. The 2014 Lok Sabha elections witnessed a significant usage of social media by political parties and leaders, especially the BJP and their then PM designate Narendra Modi to disseminate their ideology, policies and programmes and highlight the shortcomings / corruption-related scandals of the previous regime. All this helped in creating what is called the ‗Modi wave‘, and led to BJP sweeping the 2014 polls. After 2014, most political parties realised the importance of social media and registered their presence on platforms like Facebook, Twitter, Instagram. About 65 percent of India‘s population is within the age group 18-35. This group spends almost 4 hours on the internet. Political parties are therefore targeting this group of voters for mobilisation, as most of them use Twitter / Facebook to consume news. This paper represents various issues, methodologies, techniques and research work carried out for election prediction